Open Innovation Adoption In Malaysian Small Medium Enterprises - Annamalah, Sanmugam (2019)
As the world moves further into the digital age, generating innovative products will be a greater need for SMEs to survive in a competitive environment. This can be achieved by accessing and adopting the latest technology through external knowledge. The passions are to discover and develop tools to break down barriers of accessibility for SMEs in enhancing productivities through open innovation adoption. There have been studies on the success and failure of open innovation adoption, nevertheless not much research has been conducted on factors that influence open innovation adoption. The open innovation concept is a comparatively new model, where there is absence of empirical evidence to support the factors that affect open innovation, especially in terms of behavioural and costs terms. As such, this study aims to bridge the gap in the body of literature pertaining to behavioural and cost factors that impact open innovation adoption with an appropriability regime as a moderating factor in determining the success of adoption. With the view of contributing to the existing knowledge base, this research was undertaken to study the effects of organisational citizenship behaviours, organizational culture, managerial ties and transactional cost as (predictor variables) on open innovation adoption (criterion variable) and to study the moderating role of the appropriability regime on these relationships. The research uses cross-sectional data from survey mode on 376 SMEs in Malaysia. A simple random sampling technique was used and PLS-SEM regression employed to test the related hypothesis variables. The theories adopted in this research are social exchange theory and the actor-network theory that paves the ways for quantitative research. The results revealed that organizational citizenship behaviours predict open innovation positively and significantly. Highly integrative culture was found to relate positively to open innovation. In addition, managerial ties and transactional costs were found to facilitate open innovation.